Euclid preparation: LXXVII. The NISP spectroscopy channel: Ground performance and calibration - Gillard, W.; Maciaszek, T.; Prieto, E.; Grupp, F.; Costille, A.; Jahnke, K.; Clemens, J.; Dusini, S.; Carle, M.; Sirignano, C.; Medinaceli, E.; Ligori, S.; et al. (EDP Sciences, 2026)
ESA’s Euclid cosmology mission relies on the very sensitive and accurately calibrated spectroscopy channel of the Near-Infrared Spectrometer and Photometer (NISP). With three operational grisms in two wavelength intervals, NISP provides diffraction-limited slitless spectroscopy over a field of 0.57 deg2. A blue grism, BGE, covers the wavelength range 926–1366 nm at a spectral resolution (ℛ) of 440–900 for a 0.″5 diameter source with a dispersion of 1.24 nm px−1. Two red grisms, RGE, span 1206 to 1892 nm at ℛ = 550–740 and a dispersion of 1.37 nm px−1. We describe the construction of the grisms as well as the ground testing of the flight model of the NISP instrument, where these properties were established.
Key words: instrumentation: spectrographs / space vehicles: instruments / techniques: imaging spectroscopy / techniques: spectroscopic / cosmology: observations
Publisher note: The article number in this series contained a typo. The Roman numeral in the subtitle was corrected on 25 March 2026.